A Point-Based Layout for Large Hierarchies - Schulz, Hans-Jörg; Hadlak, Steffen; Schumann, Heidrun (InfoVis'08: Poster at the IEEE Conference on Information Visualization, 2008)
Space-filling layout techniques for tree representations are frequently used when the available screen space is small or the data set is large. In this paper, we propose a new approach to space-filling tree representations, which uses mechanisms from the point-based rendering paradigm. We also numerically evaluate our new technique together with two established space-filling techniques using the measures of the Ink-Paper-Ratio and overplotted